2016
DOI: 10.1172/jci.insight.87238
|View full text |Cite
|
Sign up to set email alerts
|

Blood transcriptomic diagnosis of pulmonary and extrapulmonary tuberculosis

Abstract: BACKGROUND. Novel rapid diagnostics for active tuberculosis (TB) are required to overcome the time delays and inadequate sensitivity of current microbiological tests that are critically dependent on sampling the site of disease. Multiparametric blood transcriptomic signatures of TB have been described as potential diagnostic tests. We sought to identify the best transcript candidates as host biomarkers for active TB, extend the evaluation of their specificity by comparison with other infectious diseases, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 31 publications
5
93
1
1
Order By: Relevance
“…We 9-11 and others 10- 20 have since shown that elevated and sustained levels of type I IFN, result in an enhanced mycobacterial load and disease exacerbation in experimental models of TB. Similar findings of a blood signature in active TB patients have since been reported [21][22][23][24][25][26][27] , and our meta-analysis of 16 datasets, including many of these studies, identified 380 genes differentially abundant in active TB across all datasets 28 . However, there is a relative lack of concordance across studies that have reported a reduced and optimised diagnostic gene signature, although agreement exists for some of the pathways they represent [21][22][23]29,30 .…”
Section: Introductionsupporting
confidence: 86%
“…We 9-11 and others 10- 20 have since shown that elevated and sustained levels of type I IFN, result in an enhanced mycobacterial load and disease exacerbation in experimental models of TB. Similar findings of a blood signature in active TB patients have since been reported [21][22][23][24][25][26][27] , and our meta-analysis of 16 datasets, including many of these studies, identified 380 genes differentially abundant in active TB across all datasets 28 . However, there is a relative lack of concordance across studies that have reported a reduced and optimised diagnostic gene signature, although agreement exists for some of the pathways they represent [21][22][23]29,30 .…”
Section: Introductionsupporting
confidence: 86%
“…Blood transcriptomes of patients presenting to hospital with febrile illnesses [24] confirmed that different modules associated with the same cell type show striking heterogeneity in their covariance with actual cell counts (Fig 5A). As hypothesised, MDI scores for neutrophils, T cell and B cell modules each showed excellent correlation with the covariance between module expression and cell frequency (Fig 5B–5D).…”
Section: Resultsmentioning
confidence: 89%
“…The eight signatures that achieved equivalent performance were discovered with the primary intention of diagnosis of incipient TB [16][17][18] , or differentiating active TB from people who are healthy or with LTBI 12,13,30,37 .…”
Section: Eight Signatures Have Equivalent Diagnostic Accuracy For Incmentioning
confidence: 99%
“…Discovery populations for these eight signatures included adults or adolescents from the UK or Southern Africa 12,13,[16][17][18]30 , or a meta-analysis of microarray data from multiple studies 11 , including a minimum of 37 incipient or active TB cases. All eight signatures were discovered using genome-wide approaches.…”
Section: Eight Signatures Have Equivalent Diagnostic Accuracy For Incmentioning
confidence: 99%
See 1 more Smart Citation